Single and double doping of nanostructured titanium dioxide with silver and copper : structural, optical and gas-sensing properties - Nubi, Olatunbosun Owolabi (My University, 2016)
Single and double doped nanometric powders of Single and double doped nanometric powders of titanium dioxide (TiO2) were synthesised by the sol-gel process using titanium isopropoxide (TTIP) as the precursor. For comparison, an undoped sample was also prepared. The metal dopants, Ag and Cu, were used at doping levels of 5% molar weight. The samples were dried at 100°C in air and post annealing was done at 300°C, 600°C, 900°C and 1100°C. Structural characterisation of the samples was carried out by X-ray Diffraction (XRD), Raman Spectroscopy, Scanning Electron Microscopy (SEM) and Energy dispersive X-ray Spectrometry (EDS) techniques. Most samples annealed at the 300°C temperature (and lower) revealed the predominantly-anatase phase, while those annealed at 900°C and above were rutile-only. The double-doped powder that was annealed at 300°C was found to be constituted by anatase and brookite phases (with the dopants incorporated into the TiO2 matrix), and the one annealed at 600°C was a mixture of brookite and rutile. The results suggest that multiple doping of titania may favour a two-phase structure at lower temperatures than singly-doped powders. The co-existence of brookite with anatase is believed to be responsible for the enhancement of anatase to rutile transformation in the double-doped sample. UV-visible (UV-vis) and Photoluminescence (PL) measurements were also carried out to study the optical properties of the TiO2 nanoparticles. This revealed the active PL band at around 440 nm. By narrowing the band gap, the double-doped powders that exhibited the brookite phase, again showed improved visible light photo absorption over the other samples, with a significant shift of the absorption edge to shorter wavelengths. Further, PL spectra revealed a change in PL intensity with phase change, as well as the presence of exciton energy levels at the base of the conduction band. The changes in the electrical conductivities of representative anatase and rutile TiO2 nanopowders upon exposure to water-vapour, ammonia (NH3) and hydrogen (H2) were also investigated. Sensing measurements for water-vapour was done at room temperature for various humidity levels ranging from 5.4% RH to 88.4% RH. The detection of NH3 and H2 gases were carried out at temperatures extending from room temperature to 350°C and over concentration ranges of 25 sccm to 500 sccm and 15 v sccm to 200 sccm respectively. The gas-sensing results show that the sol-gel fabricated TiO2 nanoparticles (particularly in anatase form), has excellent fast and stable dynamic responses to humidity, NH3 and H2. They feature good sensitivities, even at a low operating temperatures. However, acceptor behaviour, for which there was a conductivity switch from n-type to p-type, was recorded for the Ag-doped rutile powders at operating temperatures of 300ºC and 350ºC. Overall, the double-doped sample annealed at 300ºC was deemed the most promising candidate for gassensing. (TiO2) were synthesised by the sol-gel process using titanium isopropoxide (TTIP) as the precursor. For comparison, an undoped sample was also prepared. The metal dopants, Ag and Cu, were used at doping levels of 5% molar weight. The samples were dried at 100°C in air and post annealing was done at 300°C, 600°C, 900°C and 1100°C. Structural characterisation of the samples was carried out by X-ray Diffraction (XRD), Raman Spectroscopy, Scanning Electron Microscopy (SEM) and Energy dispersive X-ray Spectrometry (EDS) techniques. Most samples annealed at the 300°C temperature (and lower) revealed the predominantly-anatase phase, while those annealed at 900°C and above were rutile-only. The double-doped powder that was annealed at 300°C was found to be constituted by anatase and brookite phases (with the dopants incorporated into the TiO2 matrix), and the one annealed at 600°C was a mixture of brookite and rutile. The results suggest that multiple doping of titania may favour a two-phase structure at lower temperatures than singly-doped powders. The co-existence of brookite with anatase is believed to be responsible for the enhancement of anatase to rutile transformation in the double-doped sample. UV-visible (UV-vis) and Photoluminescence (PL) measurements were also carried out to study the optical properties of the TiO2 nanoparticles. This revealed the active PL band at around 440 nm. By narrowing the band gap, the double-doped powders that exhibited the brookite phase, again showed improved visible light photo absorption over the other samples, with a significant shift of the absorption edge to shorter wavelengths. Further, PL spectra revealed a change in PL intensity with phase change, as well as the presence of exciton energy levels at the base of the conduction band. The changes in the electrical conductivities of representative anatase and rutile TiO2 nanopowders upon exposure to water-vapour, ammonia (NH3) and hydrogen (H2) were also investigated. Sensing measurements for water-vapour was done at room temperature for various humidity levels ranging from 5.4% RH to 88.4% RH. The detection of NH3 and H2 gases were carried out at temperatures extending from room temperature to 350°C and over concentration ranges of 25 sccm to 500 sccm and 15 v sccm to 200 sccm respectively. The gas-sensing results show that the sol-gel fabricated TiO2 nanoparticles (particularly in anatase form), has excellent fast and stable dynamic responses to humidity, NH3 and H2. They feature good sensitivities, even at a low operating temperatures. However, acceptor behaviour, for which there was a conductivity switch from n-type to p-type, was recorded for the Ag-doped rutile powders at operating temperatures of 300ºC and 350ºC. Overall, the double-doped sample annealed at 300ºC was deemed the most promising candidate for gassensing.
Thesis (Ph. D. (Physics)) -- University of Limpopo, 2016.
Keywords: Titanium dioxide; Nanometric powders; Nanotechnology; Silver; Titanium dioxide; Nanostructured materials; Nanotechnology; Metal oxide semiconductors; Silver